Pengaruh edukasi terhadap pengetahuan Tentang episiotomi pada ibu hamil di Puskesmas (Jurnal Fenomena Kesehatan, 2025)
Episiotomy is often performed on primiparas because the birth canal is less elastic and difficult to stretch. However, in the second and third births, an episiotomy may also be necessary if the second or third baby is too large, the perineum is stiff, or in the case of a breech delivery that is particularly prone to bleeding. This research aims to determine the effect of education on pregnant women's knowledge about episiotomy at the Petumbea Community Health Center. This research uses a quasi-experimental method with one group pre-test and post-test. The respondent population was 30 people using a total sampling technique. Data collection was carried out through questionnaires, while data analysis used the Wilcoxon statistical test with a significance level of ? = 0.05. The pre-test results showed that almost all respondents (93.3%) had less knowledge about episiotomy as many as 28 people. After providing education, the post-test results showed an increase in respondents' knowledge, with 20 people (80.6%) in the good knowledge category, and 10 people (19.4%) in the moderate category. Testing the relationship between providing education and maternal knowledge about episiotomy resulted in a P-value of 0.000, which is less than ? = 0.05, indicating that there is a significant influence between providing education and increasing pregnant women's knowledge about episiotomy. Thus, this research confirms that there is a significant influence between providing education on increasing pregnant women's knowledge about episiotomy.